2020
DOI: 10.1186/s12917-020-02377-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the recombinant proteins RlpB and VacJ as a vaccine for protection against Glaesserella parasuis in pigs

Abstract: Background: Glaesserella parasuis, the causative agent of Glӓsser's disease, is widespread in swine globally resulting in significant economic losses to the swine industry. Prevention of Glӓsser's disease in pigs has been plagued with an inability to design broadly protective vaccines, as many bacterin based platforms generate serovar or strain specific immunity. Subunit vaccines are of interest to provide protective immunity to multiple strains of G. parasuis.Selected proteins for subunit vaccination should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For example, with the usage of antibiotics, more antibiotic resistance genes have been conferred to G. parasuis due to the fact of its evolution [ 8 , 9 ]. Moreover, the actual protection effect of some candidate vaccines in pigs is still nonideal [ 10 , 11 ]. An earlier study has shown that 10% of all experimentally infected pigs were fully resistant, suggesting that there are differences in susceptibility to G. parasuis infection in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, with the usage of antibiotics, more antibiotic resistance genes have been conferred to G. parasuis due to the fact of its evolution [ 8 , 9 ]. Moreover, the actual protection effect of some candidate vaccines in pigs is still nonideal [ 10 , 11 ]. An earlier study has shown that 10% of all experimentally infected pigs were fully resistant, suggesting that there are differences in susceptibility to G. parasuis infection in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on amino acid sequence analysis, the mlaA sequence is highly conserved even when a bacterium is isolated from a different host. Comparative analysis of different strains of Pasteurella multocida [ 81 ] and Glaesserella parasuis [ 82 , 83 ] show 99.6 to 100% identity in amino acid sequences within species. The retrieved NCBI sequences from Indian strains of P. multocida (cattle, buffalo, duck, pig, sheep, quail, rabbit, chicken and turkey) show > 98% amino acid similarity, and proline, aspartic acid, glutamic acid, serine and threonine are the variable amino acids [ 84 ].…”
Section: Mlaa An Om Lipoprotein Of the Mla Systemmentioning
confidence: 99%
“…Focusing on the impairment in colony morphotype, Burkholderia ( B. dolosa PC543 and B. cenocepacia K56-2) produce smaller colonies on LB agar in the absence of mlaA , whereas in P. aeruginosa [ 13 ], X. citri subsp. citri [ 82 ] and E. coli K-12 [ 13 ], no phenotypic differences were visualized.…”
Section: Impact Of Mlaa On Cell Phenotypes and Membrane Vesicles (Mv)...mentioning
confidence: 99%
“…G. parasuis negatively affects the modern swine industry and is an important bacterial disease that should be prevented [ 29 , 30 ]. Glässer’s disease has traditionally been prevented using intensive feeding management techniques, antibiotics, and inactivated vaccines [ 10 , 20 ]. Antibiotics exert a certain protective effect against Glässer’s disease.…”
mentioning
confidence: 99%